Variation in cartilage T2 and T2* mapping of the wrist: a comparison between 3- and 7-T MRI - Heiß, Rafael; Weber, Marc André; Balbach, Eva; Hinsen, Maximilian; Geißler, Frederik; Nagel, Armin Michael; Ladd, Mark E.; Arkudas, Andreas; Horch, Raymund E.; Gall, Christine; Uder, Michael; Roemer, Frank (European Radiology Experimental, 2023)
Background: To analyze regional variations in T2 and T2* relaxation times in wrist joint cartilage and the triangular fibrocartilage complex (TFCC) at 3 and 7 T and to compare values between field strengths. Methods: Twenty-five healthy controls and 25 patients with chronic wrist pain were examined at 3 and 7 T on the same day using T2- and T2*-weighted sequences. Six different regions of interest (ROIs) were evaluated for cartilage and 3 ROIs were evaluated at the TFCC based on manual segmentation. Paired t-tests were used to compare T2 and T2* values between field strengths and between different ROIs. Spearman’s rank correlation was calculated to assess correlations between T2 and T2* time values at 3 and 7 T. Results: T2 and T2* time values of the cartilage differed significantly between 3 and 7 T for all ROIs (p ≤ 0.045), with one exception: at the distal lunate, no significant differences in T2 values were observed between field strengths. T2* values differed significantly between 3 and 7 T for all ROIs of the TFCC (p ≤ 0.001). Spearman’s rank correlation between 3 and 7 T ranged from 0.03 to 0.62 for T2 values and from 0.01 to 0.48 for T2* values. T2 and T2* values for cartilage varied across anatomic locations in healthy controls at both 3 and 7 T. Conclusion: Quantitative results of T2 and T2* mapping at the wrist differ between field strengths, with poor correlation between 3 and 7 T. Local variations in cartilage T2 and T2* values are observed in healthy individuals. Relevance statement: T2 and T2* mapping are feasible for compositional imaging of the TFCC and the cartilage at the wrist at both 3 and 7 T, but the clinical interpretation remains challenging due to differences between field strengths and variations between anatomic locations. Key points: •Field strength and anatomic locations influence T2 and T2* values at the wrist. •T2 and T2* values have a poor correlation between 3 and 7 T. •Local reference values are needed for each anatomic location for reliable interpretation. Graphical Abstract: [Figure not available: see fulltext.]
CRIS-Team Scopus Importer:2023-12-22
Keywords: Cartilage (articular); Image processing (computer-assisted); Magnetic resonance imaging; Triangular fibrocartilage; Wrist joint